Formability characterization of aluminium AA6082-O sheet metal by uniaxial tension and Erichsen cupping tests - T. Nghishiyeleke, Eliaser; M. Mashingaidze, Melvin; A. Ogunmokun, Adedayo (International Journal of Engineering and Technology, 2019)
AA6082 is a relatively new structural alloy in the 6000 aluminium alloy series. This study evaluated the deep drawability of AA6082-O sheet metal. Uniaxial Tensile tests were conducted on specimens prepared according to DIN 50125-E standard, for three angular orienta-tions (0â°, 45â°, and 90â°) relative to the rolling direction. Erichsen Cupping tests were conducted on 60 mm Ã— 60 mm blanks of two gauge thicknesses (1.0 mm and 2.0 mm) and also on segmented blanks. A WP 300 Universal Material Tester, with a loading capacity of 20 kN, was used for all the tests. The Tensile Strength was higher in the rolling direction (0â°) than in the transverse orientations (45â° and 90â°). The resultant Forming Limit Curve (FLC) level of the established Forming Limit Diagrams (FLDs) was higher for the 2.0 mm thick blanks than the 1.0 mm thick blanks. Thus the alloyâ€™s formability is affected by the sheet thickness and orientation. It increases with sheet thickness, but the alloy exhibits planar anisotropy (âˆ†r
Keywords: Aluminium AA6082-O Sheet Metal; Erichsen Cupping Test; Formability; Forming Limit Diagrams; Uniaxial Tensile Test.